1992
DOI: 10.1080/00332747.1992.11024598
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Treatment Team as a Work Group: Team Dynamics and the Role of the Leader

Abstract: Although treatment teams have been examined often in the mental health literature, this literature seldom addresses the crucial property of "teamness"--the key set of intangible phenomena that allow a team to function synergistically as more than the sum of its parts, and with a sense of team identity. In this paper, the concept of the work group is used to develop a framework for understanding the factors contributing to effective team functioning and identity, an their implications for the tasks of team lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…This study showed that the leader of the SARS team played an important role in coordinating services [5]. Being in the leader's position, she had to bridge the gap between the hospital command center and the nurses.…”
Section: Discussionmentioning
confidence: 94%
“…This study showed that the leader of the SARS team played an important role in coordinating services [5]. Being in the leader's position, she had to bridge the gap between the hospital command center and the nurses.…”
Section: Discussionmentioning
confidence: 94%
“…Charismatic authority is based upon the personal characteristics of a n individual, and is related to the psychological mechanisms t h a t foster group cohesiveness (Tourquet, 1974;Wong, 1981;Yank et al, 1992a).…”
Section: Subsystdiandleadersmentioning
confidence: 99%
“…organizations (Yank et al 1992a). Their REATMENT TEAMS ARE work groups effective hnctioning is key to their parent that perform key productive tasks organizations' successful operation; yet within mental health care such teams are susceptible t o various forms of dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Lichtenstein, Alexander, Jinnett, & Ullman, 1997, p. 415) However, it is increasingly apparent that when diverse professionals are brought together to work as a treatment team, they are ineffective and, according to Yank, Barber, Hargrove, and Whitt (1992), lack a sense of "teamness." This is due, in part, to the team members' confusion of their roles, competition for authority and value, conflict or uncertainty about team tasks, ambiguity about team philosophy and model of care, and divided loyalties between their discipline and their team (Øvretveit, 1996;Whyte & Brooker, 2001;Yank, Barber, & Spradlin, 1994).…”
mentioning
confidence: 97%